Left Ventricular Unloading During Extracorporeal Membrane Oxygenation in Patients With Cardiogenic Shock - Russo, Juan J; Aleksova, Natasha; Pitcher, Ian; Couture, Etienne; Parlow, Simon; Faraz, Mohammad; Visintini, Sarah; Simard, Trevor; Di Santo, Pietro; Mathew, Rebecca; So, Derek Y; Takeda, Koji; et al. (Journal of the American College of Cardiology, 2019)
Venoarterial extracorporeal membrane oxygenation (VA-ECMO) is a widely used form of mechanical circulatory support in patients with refractory cardiogenic shock. A common drawback of this modality is a resultant increase in left ventricular afterload. The purpose of this meta-analysis was to examine the efficacy and safety of left ventricular unloading strategies during VA-ECMO in adult patients with cardiogenic shock. The authors performed a systematic search of studies examining left ventricular unloading during VA-ECMO in Medline, EMBASE, and the Cochrane library. The primary outcome was all-cause mortality. Secondary outcomes included limb ischemia, bleeding, need for renal replacement therapy, multiorgan failure, stroke or transient ischemic attack, and hemolysis. Of 2,221 publications identified, 17 observational studies met the inclusion criteria. In total, outcomes in 3,997 patients were included with 1,696 (42%) receiving a concomitant left ventricular unloading strategy while on VA-ECMO (intra-aortic balloon pump 91.7%, percutaneous ventricular assist device 5.5%, pulmonary vein or transseptal left atrial cannulation 2.8%). There were 2,412 deaths (60%) in the total cohort. Mortality was lower in patients with (54%) versus without (65%) left ventricular unloading while on VA-ECMO (risk ratio: 0.79; 95% confidence interval: 0.72 to 0.87; p < 0.00001). Hemolysis was higher in patients who underwent VA-ECMO with left ventricular unloading. Otherwise, secondary outcomes were not demonstrably different in patients treated with VA-ECMO with versus without left ventricular unloading. In observational studies, left ventricular unloading was associated with decreased mortality in adult patients with cardiogenic shock treated with VA-ECMO. In the absence of prospective randomized data, left ventricular unloading may be considered for appropriately selected patients undergoing VA-ECMO support.